Association of MIF rs1007888 and ARAP1 rs1552224 genetic variants with the risk of gestational diabetes mellitus in a chinese population; case study and meta-analysis - Zhang, Yuxuan; Wu, Yanying; Zeng, Qiaoli; Gyan, Watson Ray; Huang, Sining; Dai, Xiner; Liu, Jia; Liu, Xin; Wei, Yue; Guo, Runmin (Frontiers in Endocrinology, 2025)
BackgroundMacrophage migration inhibitory factor (MIF) rs1007888 is significantly associated with pancreatic β-cell function and insulin resistance in patients with gestational diabetes mellitus (GDM). The ArfGAP with RhoGAP domain, ankyrin repeat, and PH domain-containing protein 1 (ARAP1) rs1552224 locus has been identified as a risk locus for type 2 diabetes, and recent reports have linked it to elevated blood glucose levels and reduced insulin release upon glucose stimulation. Few studies have been conducted on these genetic variants and their risk of GDM. This study aimed to investigate the association between these two genetic variants (ARAP1) rs1552224 and (MIF) rs1007888 and the risk of developing GDM.MethodsA case-control study involving 500 GDM patients and 502 healthy controls was conducted. DNA was extracted, and rs1007888 and rs1552224 were systematically genotyped using the SNPscan™ genotyping kit. Statistical methods assessed genotype and allele differences linked to GDM risk, followed by a meta-analysis to evaluate the impact of regional factors on GDM.ResultsAnalyses of (MIF) rs1007888 showed no link to higher GDM risk, but meta-analysis found a significant association (OR>1), indicating a connection to increased GDM risk. ARAP1 rs1552224 was significantly linked to reduced GDM incidence (Allele Model A vs. C: OR = 0.624; 95% CI: 0.425-0.916; p-value = 0.016; Dominant Model AA vs. AC+CC: OR = 0.641; 95% CI: 0.429-0.959; p-value = 0.030), especially in women under 30, rs1552224 Aelle Model (A vs. C: OR = 0.490; 95% CI: 0.281-0.857; p -value = 0.012), Dominant Model (AA vs. AC + CC: OR = 0.523; 95% CI: 0.292-0.938; p -value = 0.030). and those with a BMI≥24, Aelle Model (A vs. C: OR = 0.345; 95% CI: 0.124-0.960; p-value = 0.042). Conversely, a meta-analysis suggested an increased GDM risk with the ARAP1 variant (OR>1).ConclusionThe meta-analysis results demonstrate that there is an enhanced likelihood of GDM associated with the MIF rs1007888 mutation. Moreover, our findings indicate that the ARAP1 rs1552224 variant, specifically the AC genotype and C allele, confers a decreased risk of developing gestational diabetes mellitus (GDM). The outcomes obtained give GDM testing a theoretical foundation.